2018
DOI: 10.18805/ijare.a-4978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intergrated nutrient management on acidlime [Citrus aurantifolia. Swingle (L.)]

Abstract: The nutritional need of acid lime is unique and differs from other fruit crops as it has continuous flowering and heavy fruiting habit. An experiment was conducted with the key objective of studying the effect of integrated nutrient management system on yield and quality of acid lime, variety PKM 1. In this study, application of 100 per cent recommended dose of fertilizers (600:200:300 g NPK plant-1 year-1 )+ Azospirillum (100g plant-1) + phosphobacteria (100g plant-1) + Arbuscular Mycorrizhal Fungi (500g pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…Days Taken to 50% Flowering: Treatment T6 observed the 34.1 days to reach 50% flowering, while treatment T1 and T7 taken the comparatively few days longer. This result was in conformity with the findings of Prabhu et al [2] found the application of vermicompost along with inorganic fertilizers induced less number of days taken to first flowering.…”
Section: Average Number Of Leaves Per Plantsupporting
confidence: 93%
See 1 more Smart Citation
“…Days Taken to 50% Flowering: Treatment T6 observed the 34.1 days to reach 50% flowering, while treatment T1 and T7 taken the comparatively few days longer. This result was in conformity with the findings of Prabhu et al [2] found the application of vermicompost along with inorganic fertilizers induced less number of days taken to first flowering.…”
Section: Average Number Of Leaves Per Plantsupporting
confidence: 93%
“…In order to substantiate the significance of the present study, it is valuable to briefly discuss noteworthy research endeavours undertaken by various practitioners in a similar manner. Prabhu et al [2] applied an INM approach for cucumber cultivation in winter season in Tamil Nadu, achieving appreciable productivity with a recorded yield of 32.80 tons per hectare (ton/ha) and a Benefit-to-Cost ratio of 2.24. Anjanappa et al [3] conducted an experiment in Karnataka to investigate the influence of organic, inorganic, and biofertilizers on the yield and economics of cucumber cultivation under protected conditions.…”
Section: Introductionmentioning
confidence: 99%
“…in a study on the effect of soil texture on the production and water use e ciency of greenhouse cucumber stated that the effect of texture was signi cant at the probability level of 5%. Prabhu et al (2006) in a study stated that the effects of different fertilizer levels on cucumber yield were signi cant at the probability level of 1%.…”
Section: Resultsmentioning
confidence: 99%
“…W hereas maximum number of fruits/ tree (21), Maximum average fruit weight (190.10 gm), Maximum fruit length (7.10 cm), Maximum fruit diameter (7.15 cm), Maximum fruit volume (192.13), Maximum fruit yield/tree (3.99Kg),Fruit yield/ha (199.58 q) has been obtained with treatment T14 (Azotobacter + 75% Nitrogen through urea + 25% Vermicompost). Prabhu et al (2018) studied the effect of integrated nutrient management on acid lime [Citrus aurantifolia. Swingle (L.)] and concluded that application of 100 per cent recommended dose of fertilizers (600:200:300 g NPK plant -1 year -1 ) + Azospirillum (100 g plant -1 ) + phosphobacteria (100 g plant -1 ) + Arbuscular Mycorrizhal Fungi (500 g plant -1 ) + Trichoderma harzianum (100 g plant -1 ) has showed a superior performance regarding yield, yield attributing components and quality attributes of acidlime.…”
Section: Impact Of Integrated Nutrient Managementmentioning
confidence: 99%